Morphosemantic Study Of Compound Words In The New York Times Articles - Karen Maria Ekafrain Aring; I Wayan Arka; I Nyoman Sedeng (Universitas Palan, 2023)
The New York Times is USA’s most popular digital news platform which can be accessed easier by people around the world. Due to many new words that can be combined to become compound words, it is interesting to see the compound words that are applied on the New York Times website. This study looked at the different the types and meanings of compound words used in the New York Times articles. The study describes the types of compound words with the theory proposed by Katamba (1993). Then, to analyze the meanings of compound words, the theory by Palmer (1991) was used. To achieve the objectives, descriptive qualitative methods were used in the study. The data were taken from the New York Times website. In collecting data, the documentation method with note-taking techniques was applied. From 58 data collected, the results showed that compound nouns become the most common types of compound words used in the articles with 33 compound words, followed by compound verbs with 13 compound words, and compound adjectives with 12 compound words. Referring to the meaning of compound words, there are 34 compound words with opaque meanings and 24 compound words with transparent meanings.